2023
DOI: 10.1038/s41598-023-30771-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of hemorphins with ACE homologs

Abstract: Hemorphins, short bioactive peptides produced by enzymatic cleavage of β-hemoglobin, exhibit antihypertensive properties by inhibiting angiotensin-1 converting enzyme (ACE1). ACE1 is a key player in the renin–angiotensin system (RAS) and regulates blood pressure. ACE1 and its homolog, ACE2, which exhibit opposing activities in the RAS, share considerable similarity in their catalytic domains. The primary objective of this study was to identify and contrast the molecular mechanisms underlying the interaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…It was observed that DLGGFFGFQR formed eight hydrogen bonds with amino acids Cys352, Gln369, Val380, Pro407, His410, Gly408, and Gly414 in ACE, and the residues may enhance the ability of ACE to immobilize peptides and enhance stability, which may lead to increased inhibition. Based on relevant experimental reports and the findings related to the catalytic mechanism of ACE, it could be inferred that the results were similar to those for hemorphins [46]. Furthermore, DLGGFFGFQR formed 27 hydrophobic interactions with ACE and the action sites exhibited were different.…”
Section: Molecular Docking Conformation Analysissupporting
confidence: 60%
“…It was observed that DLGGFFGFQR formed eight hydrogen bonds with amino acids Cys352, Gln369, Val380, Pro407, His410, Gly408, and Gly414 in ACE, and the residues may enhance the ability of ACE to immobilize peptides and enhance stability, which may lead to increased inhibition. Based on relevant experimental reports and the findings related to the catalytic mechanism of ACE, it could be inferred that the results were similar to those for hemorphins [46]. Furthermore, DLGGFFGFQR formed 27 hydrophobic interactions with ACE and the action sites exhibited were different.…”
Section: Molecular Docking Conformation Analysissupporting
confidence: 60%
“…These molecules work as opioid receptor ligands by exhibiting affinity for μ-, δ- and k-receptors and show antinociceptive activity [ 21 ]. Effects of hemorphins on the renin-angiotensin system (RAS), the kinin-kallikrein system (KKS) and insulin-regulating aminopeptidase (IRAP) are also documented [ 22 , 23 ]. Apart from this, these peptides are also reported to modulate the activity of calcineurin and Ca 2+ /calmodulin-dependent systems [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…[11] Some hemorphins are thought to be involved in blood pressure control by blocking both angiotensinconverting enzymes. [12] The affinity of the endogenous hemorphins for insulin-regulatory aminopeptidase suggests that they may act as analogs of angiotensin IV in regulating more complex brain functions such as memory. [13] Looking through the literature, certain nonnatural amino acids have been recognized as interesting profiles due to their effects on biologically active compounds with potential application in drug design and medicinal chemistry, once they have been inserted in peptide chains as novel unnatural building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Some hemorphins are thought to be involved in blood pressure control by blocking both angiotensin‐converting enzymes. [ 12 ] The affinity of the endogenous hemorphins for insulin‐regulatory aminopeptidase suggests that they may act as analogs of angiotensin IV in regulating more complex brain functions such as memory. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%